Pathway to care among clients attending at psychiatric out patient department of a teaching hospital, Bharatpur - Pokharel, Sindu; Subba, Ramesh; Subba, Hem Kumari (Journal of Chitwan Medical College, 2022)
Background: Mental illnesses cause significant suffering around the world. A limited number of people with psychiatric problems seek treatment in healthcare facilities when their condition is severe only. Treatment by faith healers and unqualified medical practitioners is frequent which lead to the delay in proper treatment. The objective of the study was to identify the pathway to care among clients attending at Psychiatric Outpatient Department of Chitwan Medical College, Teaching Hospital, Bharatpur. Methods: Descriptive cross-sectional design was used and 166 clients attending at psychiatric OPD of Chitwan Medical College, Teaching Hospital were selected by using non-probability, consecutive sampling technique. Data were collected from 11th August 2019 to 6th September 2019 through face to face interview method using structured interview schedule. Collected data were further analyzed in SPSS version 23 using descriptive and inferential statistics Results: The finding of the study revealed that 54.2% of clients first visited faith healer for initial treatment and only 16.9% visited psychiatrist directly for the treatment. Similarly, 53.6% of clients visited other personnel than psychiatrist due to their cultural belief and 59.6% of the clients had adequate level of awareness towards mental illness. Significant association was found between status of pathway to care and client’s sex, ethnic group and occupation. Conclusions: It is concluded that mental illness clients first approached faith healer for their initial treatment due to their cultural belief. It is important that traditional healers and other treatment providers must be aware of and recognize the mental illnesses in order to treat mental patients early and refer to psychiatrist.